Snapdragons: locked out - Bennett, Leonie; Adams, Arlene (Oxford University Press UK, 2004)
When Gran and Suzy are locked out of the house, they try the door and windows, but can't get in. Finally Suzy follows Boxer through the dog flap, and gets inside